2002
DOI: 10.1002/ijc.10549
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lung cancer among nonsmoking women

Abstract: To evaluate risk factors for lung cancer in nonsmoking women, we used data of a case-control study conducted between 1991 and 1996 in Germany. A total of 234 female histologically confirmed lung cancer patients and 535 population controls who had never smoked more than 400 cigarettes in their lifetime were personally interviewed with respect to occupation, exposure to environmental tobacco smoke (ETS), family history of cancer, prior physician-diagnosed lung diseases or cancer and diet. One-year radon measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(63 citation statements)
references
References 43 publications
4
54
0
5
Order By: Relevance
“…The authors suggest that lung cancer, smoking, and environmental tobacco smoke exposure aggregate in families. A German study found a significantly increased risk for exposure to environmental tobacco smoke at work [38]. However, a non-significant increase in risk was found for spousal exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that lung cancer, smoking, and environmental tobacco smoke exposure aggregate in families. A German study found a significantly increased risk for exposure to environmental tobacco smoke at work [38]. However, a non-significant increase in risk was found for spousal exposure.…”
Section: Discussionmentioning
confidence: 99%
“…22 As for possible risk factors for lung cancer among nonsmokers, these were not defined but could have been radon, air pollution and dietary factors such as meat and fat. 13 Comparing the highest and lowest vegetable consumption frequencies, the difference in risk was 2-3-fold.…”
Section: Discussionmentioning
confidence: 99%
“…1 Although the relation between respiratory Chlamydia psittaci infection (avian exposure) and female lung cancer remains open, [2][3][4] C. pneumoniae infection has been repeatedly shown to be associated with lung cancer in male smokers as defined by serum cotinine. [5][6][7] We have now evaluated the association between past infection with C. pneumoniae and female lung cancer in a case-control study nested in a cohort of 650,000 fertile Finnish women established in 1983.…”
Section: Dear Sirmentioning
confidence: 99%